IDENTIFIKASI RESIKO TITIK KRITIS KEHALALAN PADA PRODUK KOPI BUBUK - Elke Stephanie; Siti Irma Rahmawati (Universitas Djuanda, 2020)
Halal has already become one of requirements for food products in order to penetrate the global market, including in Indonesia. The Indonesian government establishes halal certification obligations for all incoming, outstanding and traded products in the territory of Indonesia. The halal audit and certification stages of processed food are complex and have an impact on a low halal risk. Coffee is a plantation commodity which has a high economic value and plays an important role as a source of foreign exchange for the country. One of the processed coffee products that are often found is ground coffee. This study aims to determine the critical point of ground coffee products to control the risk of non-halal products. This research was conducted in 2 (two) stages, namely making flowcharts or production process flowcharts and identifying the risk of critical points for ground coffee products. The results of the study show that the critical point in the manufacture of ground coffee lies in the roasting process which is mixed with other ingredients, for example butter fat and the facilities used must be free from contamination of non-halal and unclean materials. The critical point in ground coffee products in the form of sachets is at the stage of adding additives. The halalness of other ingredients need to be considered especially related to the origin (source) and how to obtain it. Keywords: Halal, Critical Point, Coffee.